CTNNB1 Mutations and Estrogen Receptor Expression in Neuromuscular Choristoma and Its Associated Fibromatosis. (October 2016) - Carter, Jodi M.; Howe, Benjamin M.; Hawse, John R.; Giannini, Caterina; Spinner, Robert J.; Fritchie, Karen J.
Abstract : Neuromuscular choristoma (NMC) is a very rare, developmental malformation characterized by the endoneurial intercalation of mature muscle fibers among peripheral nerve fibers. NMC typically arises in the major proximal peripheral nerves, most commonly the sciatic nerve, and may involve the lumbosacral and brachial plexus. Patients present clinically with progressive neuropathy or plexopathy. NMC is strongly associated with development of a fibromatosis, histologically identical to conventional desmoid-type fibromatosis (NMC-fibromatosis). The development of NMC-fibromatosis is often precipitated by iatrogenic trauma (ie, biopsy). Desmoid-type fibromatosis is characterized by CTNNB1 exon 3 mutations, which result in aberrant nuclear β-catenin localization and dysregulated canonical Wnt signaling. In contrast, the pathogenesis of NMC and NMC-fibromatosis is unknown. Desmoid-type fibromatosis expresses estrogen receptors (ER), specifically the ER-beta isoform (ERβ), and endocrine therapies may be used in surgically unresectable cases. In contrast, the ER expression profile of NMC-fibromatosis is unknown. We evaluated a series of NMC and NMC-fibromatosis for CTNNB1 mutations, β-catenin expression, and ER isoform expression. Five NMCs occurred in 2 female and 3 male patients (median age: 14 y, range <1 to 42 y), as masses involving the sciatic nerve (N=4) or brachial plexus (N=1). Four (of 5) NMCs had CTNNB1 mutations: 3 c.134 C>T (p.S45F) and 1 c.121 A>G (p.T41A). Four patients subsequently developed NMC-fibromatosis, and all 4 cases contained CTNNB1 mutations, including 1 p.T41A and 3 p.S45F mutations. In 3 patients, the NMC and NMC-fibromatosis had identical CTNNB1 mutations. Only 1 NMC had no detectable CTNNB1 mutation; however, the patient's subsequent NMC-fibromatosis had a CTNNB1 p.T41A mutation. All NMC and NMC-fibromatosis showed aberrant nuclear localization of β-catenin, nuclear ERβ expression, and no ERα expression. The presence of CTNNB1 mutations both in NMC and NMC-fibromatosis may be a shared molecular genetic abnormality underlying their pathogenesis.